Anti-Diabetic Effect of Gymnema Sylvestre On Streptozotocin-Induced Diabetic Rats - Singh, Ankita; Suryawanshi, Renuka Madhav; Shukla, Divaker; Som, Mehuli; Singh, Ruchi; Bhatia, Nitish; Kumar, Pramod; Akanda, Sazedur Rahman; Bhojak, Narendar (Journal of Neonatal Surgery, 2025)
Gymnemate Sylvestre (Gs), a traditional medicinal plant known for its potent anti-diabetic properties, was investigated for its therapeutic potential in streptozotocin (STZ)-induced diabetic rats. Diabetes was induced by a single intraperitoneal injection of STZ (60 mg/kg), leading to hyperglycaemia, oxidative stress, and inflammatory responses characteristic of diabetic neuropathy. Following diabetes induction, rats received oral administration of Gs leaf extract at doses of 50 mg/kg and 100 mg/kg daily for five weeks. The treatment significantly decreased blood glucose levels and improved insulin secretion, demonstrating a restorative effect on pancreatic β-cell function. Gs also attenuated oxidative stress markers, including lipid peroxidation and antioxidant enzyme activities, in sciatic nerve tissues. Additionally, proinflammatory cytokines such as TNF-α, IL-1β, and IL-6, elevated in diabetic rats, were markedly reduced upon Gs treatment. Histopathological analysis revealed improvement in nerve tissue structure, indicating neuroprotective effects. The study supports that Gymnemate Sylvestre exerts multi-targeted anti-diabetic effects by modulating hyperglycaemia, oxidative stress, inflammation, and enhancing nerve growth factors. These findings highlight Gs as a promising natural therapeutic agent for diabetes management and its complications, especially diabetic neuropathy, warranting further clinical exploration